Literasi Pemanfaatan Olahan Sampah Organik Rumah Tangga pada Kelompok Mangga RT 30 Kelurahan Sawah lebar Baru - Hoten, Hendri Van; Nurbaiti; Helmizar (Universitas Bengkulu, 2024)
As we all know, waste is a problem in daily life. The problem of waste that often occurs is the mixing or not being separated between organic and non-organic waste. The variety of organic waste is abundant and rich in minerals needed for soil fertility and by plants. Therefore, the management of organic waste is strived to become a culture at the smallest environmental level. There are two types of organic waste, solid and liquid. Organic waste is useful for composting planting media, while liquid waste is useful for liquid organic fertilizer (POC). Working alone often causes boredom, no sharing environment causes monotonous knowledge, lack of motivation, no mutual cooperation and mutual reinforcement. Therefore, a systems approach is needed through the formation of groups for the utilization of the organic waste. Through the 2021 FT Unib Development Service, the formation of Environmental Organic Waste Utilization Group among neighbors is an effort that is raised so that members of this group will manage household waste in at least one type, namely the manufacture of POCs and socialization of the processing of the waste.